Do Wealthier Households Save More? – The Impact of the Demographic Factor - Ansgar Belke; Christian Dreger; Richard Ochmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper investigates the relationship between wealth, ageing and saving behaviour of private households by using pooled cross sections of German consumption survey data. Different components of wealth are distinguished, as their impact on the savings rate is not homogeneous. On average, the effect attributed to real estate dominates the other components of wealth. In addition, the savings rate strongly responds to demographic trends. Besides the direct impact of the age structure, an indirect effect arises through the accumulation of wealth. The savings rate does not decrease with age in a monotonic way, as the permanent income hypothesis suggests. Most prominently, older households tend to increase their savings in the second half of their retirement period, probably due to bequest motives and increasing immobility. Given the ongoing demographic trend, an increase of 1.4 percentage points in the aggregated savings rate should be expected over the next two decades.
Keywords: G10; G11; 330; Savings; wealth; demographic change